PEMBIAYAAN MUDHARABAH BERTINGKAT PADA BANK UMUM SYARIAH - Ahmad Zaenal Abidin; Moh. Rasyid; Rezkia Zahara Lubis (IQTISADIE: Journal of Islamic Banking and Shariah Economy, 2021)
Islamic banks in carrying out their financial activities use contracts in classical muamalat fiqh, including mudharabah contracts. The mudharabah contract which initially only brought together two parties, namely the owner of capital and the manager of capital, has now undergone a change in practice in Islamic banks. Mudharabah contracts in Islamic banks currently involve three parties, the owners of capital, the bank and the borrower of capital. This pattern of contracts involving three parties is called multilevel mudharabah. Based on these reasons, this study will discuss what and how the implementation of multilevel mudharabah in Islamic commercial banks. This research is a research qualitative with a juridical-normative approach. This study concludes that multilevel mudharabah is a form of mudharabah that occurs between three parties. The first party is the shahibul maal, the second party is the intermediate mudharib, and the third party is the final mudharib. In this contract, the bank has a dual role, namely as mudharib as well as shahibul mal. As mudharib, the bank manages the funds deposited by the depositor to seek profit. Meanwhile, as shahibul mal, the bank distributes these funds to mudharib for further management. If you look at the above understanding of the practice of this multilevel mudharabah contract, namely, when the depositor or shaahibul mal saves their funds with a mudharabah contract with a sharia bank, this practice refers to the mudharabah mutlaqah principle, there are no restrictions for banks in using the funds raised. Keywords: Mudharabah, Financing, Islamic Bank